Analysis of Foundation Reinforcement Schemes for Shield Tunnels in Wenzhou Soft Soil Strata Based on Long-term Settlement Control - GOU Changfei; XIE Botao (Chengshi guidao jiaotong yanjiu)
[Objective] After the shield tunnels in soft soil areas are put into operation, long-term settlement of the tunnel caused by various factors poses a threat on the safety of rail transit operation. Train load is one of the important causes for the long-term settlement of shield tunnels in soft soil areas. Therefore, it is necessary to study the foundation reinforcement schemes for shield tunnels. [Method] A comparative analysis is carried out on the reinforcement effects, applicable strata, difficulty levels of engineering implementation, reinforcement scopes, and reinforcement costs of the ground pre-reinforcement methods such as grouting, cement mixing piles, high - pressure jet grouting, and the in-tunnel grouting reinforcement method. Taking the foundation reinforcement scheme for the Oujiang North Estuary Tunnel of Wenzhou Rail Transit Line S2 as an example, the numerical simulation method is used to analyze the additional stress of the foundation soil caused by train loads when different foundation reinforcement schemes are adopted for the shield tunnels in soft soil areas. Through stress analysis, the influence patterns of the reinforcement width and depth at the tunnel bottom on the reinforcement effect are studied, thereby the reinforcement scheme for the Oujiang North Estuary Tunnel is determined.. Then, the effectiveness of the reinforcement scheme is verified through on-site settlement monitoring data. [Result & Conclusion] After the soft soil at the bottom of the shield tunnel is reinforced, the additional stress caused by train loads shows a stress concentration (increase) phenomenon in the reinforced area and a stress diffusion (decrease) phenomenon in the non-reinforced area. The reinforcement width has an insignificant impact on the stress concentration or diffusion effect, while the reinforcement depth has a significant impact on tunnel settlement. When the reinforcement depth exceeds a certain limit, the control effect on tunnel settlement is no longer significant.